Pemecahan Masalah Dalam Budidaya Kepiting dan Pelatihan Produksi Kepiting Karapas Lunak di Desa Kamal Bangkalan Madura - Putri, Rizka Rahmana; Triajie, Haryo; Abida, Indah Wahyuni; Zainuri, Muhammad; Hafiludin, Hafiludin; Farid, Akhmad; Muhsoni, Firman Farid; Chandra, Adyos Bobby; Junaedi, Abdus Salam; Sholeh, M.; Laksani, Mertiara Ratih Terry; Pramithasari, Febi Ayu; Afifa, Fitria Hersiana; Wati, Tarisa Sholikha; Nisrina, Nisrina; Rahman, Rahman; Faizin, Muhammad Sahrul (LPPM Universitas Trunojoyo Madura, 2024)
Soft-shell crabs are a type of crab harvested after molting or shedding their old shells. Soft-shell crabs are known for their high market value, both in domestic and international markets. Technological advancements in crab farming include the mangrove crab mutilation system to produce soft-shell crabs (soka). However, many communities still lack an understanding of this technology. The mutilation technology is known to provide benefits, so we conducted a community outreach program to impart knowledge about the molting process in crabs and provide training on how to mutilate crabs in Kamal Village. Additionally, in the crab farming process, there are issues related to water quality management and feeding. The outreach program also aims to provide solutions to these problems. The method employed is the Adult Learning Approach, which is carried out through participatory lectures and interactive discussions. Meanwhile, the crab mutilation training is conducted using the Demonstration and Example Method, where participants practice the crab mutilation process after receiving demonstrations from the facilitators. The molting process and the sustainability of the outreach program are continued with ongoing mentoring until desired outcomes are achieved.